2021
DOI: 10.1177/00222194211043482
|View full text |Cite
|
Sign up to set email alerts
|

Data Mountain: Self-Monitoring, Goal Setting, and Positive Attributions to Enhance the Oral Reading Fluency of Elementary Students With or at Risk for Reading Disabilities

Abstract: Data Mountain is a self-determination program that has shown early promise in enhancing the oral reading fluency (ORF) of students with or at-risk for reading disabilities (RD). This program supports self-determined learning behaviors through explicit teaching of self-monitoring, goal setting, and positive attributions. The present study tested the effects of Data Mountain on the ORF of 81 students with or at-risk for RD in second through fifth grades, randomly assigned to one of three conditions: Data Mountai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Moreover, students with reading challenges have been classified as passive rather than active readers who do not monitor their understanding or select strategies to aid understanding and address misunderstanding (Elleman & Oslund, 2019). Prior studies provide evidence for the use of self-monitoring, or keeping track of one's own behavior during reading (e.g., Didion & Toste, 2021). Many studies have also used a combination of strategy instruction with metacognitive approaches to support application of newly learned skills (Berkeley et al, 2010).…”
Section: Metacognitive Approachesmentioning
confidence: 99%
“…Moreover, students with reading challenges have been classified as passive rather than active readers who do not monitor their understanding or select strategies to aid understanding and address misunderstanding (Elleman & Oslund, 2019). Prior studies provide evidence for the use of self-monitoring, or keeping track of one's own behavior during reading (e.g., Didion & Toste, 2021). Many studies have also used a combination of strategy instruction with metacognitive approaches to support application of newly learned skills (Berkeley et al, 2010).…”
Section: Metacognitive Approachesmentioning
confidence: 99%
“…In contrast, manualizing lesson plans minimizes the potential for the children and their families and teachers to directly influence the instructional design in a sustained way. Locally designed instructional materials can be more readily tailored to the interests and needs of individual children, and, following a data-based intervention model (e.g., Didion & Toste, 2022; Filderman et al, 2018), can be more rapidly modified if shown to not be working for a particular child. Both approaches have value for design of instruction; our choice in developing for wide dissemination was for ease of use in important efficacy trials such as this and also given our sense of the need for educators to rapidly gain access to usable materials without necessarily having the pedagogical content knowledge with which to develop such supplemental instructional content focused on oral language, as indicated by teacher knowledge assessments (e.g., Phillips et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A procedure used to teach students to observe, record, and reinforce their own reading behaviors to strengthen accurate and fluent responding (Didion & Toste, 2022;Joseph & Eveleigh, 2011).…”
Section: Self-monitoring Proceduresmentioning
confidence: 99%